2023
DOI: 10.1128/spectrum.03144-22
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role for the Human Cytomegalovirus Major Immediate Early Proteins in Recruitment of RNA Polymerase II and H3K27Ac To an Enhancer-Like Element in Ori Lyt

Abstract: HCMV is an important human pathogen associated with complications in transplant patients and birth defects. The complex program of viral gene expression is regulated by both viral proteins and host factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 92 publications
0
6
0
Order By: Relevance
“…OriLyts in herpesviruses are somewhat conserved, and KSHV OriLyts also contain the C/EBP CCCAT domains, supporting our finding of OriLyt-L as an RTA-inducible enhancer (115). Additionally, similar to KSHV, HCMV OriLyt gives rise to two ncRNAs (100). Thus, it can be envisioned as an enhancer, giving rise to ‘enhancer-derived lncRNA’ (116118).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…OriLyts in herpesviruses are somewhat conserved, and KSHV OriLyts also contain the C/EBP CCCAT domains, supporting our finding of OriLyt-L as an RTA-inducible enhancer (115). Additionally, similar to KSHV, HCMV OriLyt gives rise to two ncRNAs (100). Thus, it can be envisioned as an enhancer, giving rise to ‘enhancer-derived lncRNA’ (116118).…”
Section: Discussionmentioning
confidence: 99%
“…A strong enhancer is located upstream of the major immediate-early gene of Human Cytomegalovirus (HCMV) (98). Additional enhancers in HCMV are located in the short unique region (99) and OriLyt (100). Even the closest relative of KSHV, the Epstein Barr Virus (EBV), contains several enhancers, including the DR enhancer, which is both constitutive and lytically induced (101).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both IE72 and IE86 bind HDAC3, which, in the case of the IE72-HDAC3 association, disrupts histone deacetylation ( 100 ), thus directly promoting active histone marks. Recently, Forte et al showed IE72 and IE86 recruit RNA polymerase II and H3K27ac to the Ori Lyt RNA4.9 promoter in lytically infected fibroblasts ( 138 ). Since Ori Lyt is a bi-directional promoter ( 139 ), Forte et al posit this IE-dependent H3K27ac enrichment at early times post-infection suggests this region functions as an enhancer element to influence E gene expression ( 138 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Forte et al showed IE72 and IE86 recruit RNA polymerase II and H3K27ac to the Ori Lyt RNA4.9 promoter in lytically infected fibroblasts ( 138 ). Since Ori Lyt is a bi-directional promoter ( 139 ), Forte et al posit this IE-dependent H3K27ac enrichment at early times post-infection suggests this region functions as an enhancer element to influence E gene expression ( 138 ). While intriguing, additional experiments are necessary to define this region of the Ori Lyt as an E gene enhancer element.…”
Section: Introductionmentioning
confidence: 99%